ANALISIS PRODUKSI USAHATANI JAGUNG DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Ilyas, Iswanto; Afandi, Afandi (AGROTEKBIS, 2016)
This study aims to determine the effect of land, seed, fertilizer, labor in corn farming in the village of Labuan Labuan Toposo District of Donggala. It was conducted in November 2015 to January 2016. The analysis of t-test showed that the partial area of land was highly significant with t count> t-table (8.705> 2.485) at a rate of 1% Î±, seeds significantly with t-count> t-table (8.701> 2.485) at the level of Î± 1%, fertilizer significantly with t count> t-table (5.319> 2.485) at the level of Î± 1% and labor significantly with t count> t-table (5.578 > 2.485) at the level of Î± 1%. Simultaneous analysis test shows land area factor (X1), seeds (X2), fertilizers (X3), and labor (X4) a very significant effect on maize with F-count> F-table (21.523> 4.177).Â Key Words : Corn, production, The Village of Â Labuan Toposo.